Assessment of Aerobic Exercise Adverse Effects during COPD Exacerbation Hospitalization. (6th February 2017) - Knaut, Caroline; Mesquita, Carolina Bonfanti; Caram, Laura M. O.; Ferrari, Renata; Dourado, Victor Zuniga; Godoy, Irma de; Tanni, Suzana Erico
Abstract : Introduction. Aerobic exercise performed after hospital discharge for exacerbated COPD patients is already recommended to improve respiratory and skeletal muscle strength, increase tolerance to activity, and reduce the sensation of dyspnea. Previous studies have shown that anaerobic activity can clinically benefit patients hospitalized with exacerbated COPD. However, there is little information on the feasibility and safety of aerobic physical activity performed by patients with exacerbated COPD during hospitalization. Objective. To evaluate the effects of aerobic exercise on vital signs in hospitalized patients with exacerbated COPD. Patients and Methods. Eleven COPD patients (63% female, FEV1: 34.2 ± 13.9% and age: 65 ± 11 years) agreed to participate. Aerobic exercise was initiated 72 hours after admission on a treadmill; speed was obtained from the distance covered in a 6-minute walk test (6MWT). Vital signs were assessed before and after exercise. Results. During the activity systolic blood pressure increased from 125.2 ± 13.6 to 135.8 ± 15.0 mmHg (p = 0.004 ) and respiratory rate from 20.9 ± 4.4 to 24.2 ± 4.5 rpm (p = 0.008 ) and pulse oximetry (SpO2 ) decreased from 93.8 ± 2.3 to 88.5 ± 5.7% (p < 0.001 ). Aerobic activity was considered intense, heart rate ranged from 99.2 ± 11.5 to 119.1 ± 11.1 bpm at the end of exercise (p = 0.092 ), and patients reached on average 76% of maximum heart rate. Conclusion. Aerobic exercise conducted after 72 hours of hospitalization in patients with exacerbated COPD appears to be safe.